Komunikasi Ritual Pandita dalam Upacara Keagamaan Hindu - Jelantik, Sayu Kadek; Subadra, Dewa Made Kutha; Sudarsana, I Wayan Putu (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2024)
Ritual communication carried out by the Pandita is an important aspect in maintaining spiritual connectedness between the people, the universe, and God. This analysis will examine how the Pandita uses symbols, language, and gestures in religious ceremonies to convey religious messages and build a deep spiritual atmosphere. The purpose of this study is to analyze the process of ritual communication of the pandita in Hindu religious ceremonies. The research method used is qualitative descriptive with data collection techniques, namely observation, interviews and documentation. The results of the study are the Central Role of the Pandita as a spiritual mediator who connects Hindus with God through religious rituals and also conveys religious and moral values. Ritual communication in Hindu religious ceremonies involves the use of symbolic language, such as mantras, and sacred objects (fire, incense, tirta) that have deep spiritual meaning. This symbolism enriches the communication process between the people, the pandita, and divine power. Mantra as Sacred Communication in Mantras spoken by the pandita in Sanskrit or Old Balinese are a form of verbal communication that is considered to have spiritual power. Non-Verbal Communication: Body movements and ritual attitudes carried out by the pandita during the ceremony are also important forms of communication. Social and Cultural Functions: Ritual communication led by the pandita plays a role in strengthening social cohesion and cultural identity in the Hindu community. Ritual ceremonies not only function as a spiritual means, but also as a medium to strengthen relationships between community members and maintain cultural heritage. Education and Transformation of Religious Values ​​act as educators who convey Hindu teachings directly through rituals. Through ceremonies, pandita teaches moral values, ethics, and religious teachings that are relevant to the lives of the people. The ritual communication of the pandita in Hindu religious ceremonies is a complex and profound process, involving various forms of communication, both verbal and non-verbal, to convey spiritual messages, strengthen social ties, and maintain the cultural identity of the Hindu people.